2019
DOI: 10.1007/s41742-019-00180-1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pH on the Treatment of Artificial Textile Wastewater Containing Azo Dyes Using Pond Systems

Abstract: Two controlled experiments were operated to evaluate the impact of pH on the treatment efficiency of azo dyes within artificial textile wastewater using ponds as a polishing step. The objectives were to assess the (1) inflow water quality; (2) the presence of Lemna minor and the algae Oedogonium spp. on the dye removal and the outflow water quality; and (3) suitability of applying artificial textile wastewater and the impact of this wastewater and the dye on plants. Findings indicate that the shallow ponds pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…used for wastewater treatment are Ulva sp., Chaetomorpha sp., Oedogonium sp., Chlorophyta sp., Spirogyra sp., and Kelp sp. Macroalgae have also been shown to remove COD and BOD from several wastewaters such as municipal (Amiri and Ahmadi 2020), textile (Yaseen and Scholz 2019), piggery effluent (Nwoba et al 2017), shrimp farm waste (Santhi and Deivasigamani 2017), palm mill oil effluent (Kamyab et al 2015), and sewage (Ashokkumar et al 2019). Macroalgae have been reported to remove heavy metals due to their higher biosorption capacities; metals such as nickel, cadmium, copper, and zinc were removed by significantly synergistic action of macro-and microalgae consortium (Piccinni et al 2019).…”
Section: Emergingmentioning
confidence: 99%
“…used for wastewater treatment are Ulva sp., Chaetomorpha sp., Oedogonium sp., Chlorophyta sp., Spirogyra sp., and Kelp sp. Macroalgae have also been shown to remove COD and BOD from several wastewaters such as municipal (Amiri and Ahmadi 2020), textile (Yaseen and Scholz 2019), piggery effluent (Nwoba et al 2017), shrimp farm waste (Santhi and Deivasigamani 2017), palm mill oil effluent (Kamyab et al 2015), and sewage (Ashokkumar et al 2019). Macroalgae have been reported to remove heavy metals due to their higher biosorption capacities; metals such as nickel, cadmium, copper, and zinc were removed by significantly synergistic action of macro-and microalgae consortium (Piccinni et al 2019).…”
Section: Emergingmentioning
confidence: 99%
“…The pH of all eco-enzyme-treated samples did not undergo significant changes after 5 days, indicating that nitrification and other processes are still going on. Low pH in wastewater after adding EE will influence the decolourization of dye [ 43 ]. As Aris et al (2007) suggested, limestone can be used to recover acidic water to water close to neutral [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Dye concentration varies extensively in textile wastewater and the treatment efficiency of EC depends on initial pollutant concentration ( Yaseen and Scholz, 2019 ). To investigate the treatment performance for variable dye concentrations, several experiments were conducted for 100, 200 and 300 mg.L −1 MO dye solutions at the optimized pH range (4–5) and at 0.11 mA cm −2 current density.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, optimum current densities for 100, 200, and 300 mg.L −1 dye solutions were determined at the optimum pH. In literature, it is mentioned that the dye concentration in textile wastewater ranged from 10 to 500 mg.L −1 ( Yaseen and Scholz, 2019 ). Therefore, the experiments were conducted for higher dye concentrations (100–300 mg.L −1 MO dye).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation